Phytochemical composition and biological activities of Asteriscus graveolens (Forssk) extracts. (May 2017) - Ramdane, Farah; Essid, Rym; Mkadmini, Khaoula; Hammami, Majdi; Fares, Nadia; Mahammed, Mahfoud Hadj; El Ouassis, Dahmane; Tabbene, Olfa; Limam, Ferid; Ould Hadj, Mohamed Didi
Graphical abstract: Highlights: Some Asteriscus graveolens fractions showed important biological activities. Ethyl acetate fractions showed the highest antioxidant potential. Ethyl acetate displayed the stronger antibacterial and antileishmanial activities. Good selectivity index and specificity for amastigote and promastigote forms. Activity was attributed to the high content of phenols compounds. Abstract: In the present study the phytochemical composition and biological activities of the aerial part extracts of Asteriscus graveolens against pathogenic bacteria and leishmania parasite were evaluated. Phytochemical analysis revealed the presence of polyphenols, flavonoids and tannins. The ethyl acetate fraction exhibited high antioxidant potential of 359.72 ± 32.03 μg and 326.76 ± 15.86 μg of ascorbic acid equivalents and 13.32 ± 0.19 μg/mL by PM, FRAP and DPPH assays respectively. This fraction also displayed a moderate antibacterial activity against Listeria monocytogenes ATCC 19115 (MIC = 0.312 mg/mL) and strong antileishmanial activity against both promastigote and amastigote forms with IC50 ranging from 22.93 ± 0.39 μg/mL to 35.23 ± 0.62 μg/mL. Furthermore the ethyl acetate fraction exhibited low cytotoxicity and good selectivity index towards the macrophage cell line Raw 264.7. HPLC analysis of the active fraction revealed the presence of hydroxycinnamic acid as major compound (30.56%). Asteriscus graveolens is a promising source of bioactive compounds that could be potentially used in cosmetic and pharmaceutical industry.